Aseptic culture free method for screening Arabidopsis transgenic seeds from in planta transformation - ZHANG Hao-fu; ZHANG Xian-yin (浙江大学学报. 农业与生命科学版)
Sterile culture is normally employed in screening in planta transformed seeds, which is both labor-intensive and contamination-prone, and material loss events often occur because of failure in sterilization. An aseptic culture free method was developed for screening Arabidopsis transgenic seeds from in planta transformation based on the traditional method by depleting sucrose and organic components unnecessary for seed germination and screening, reducing macronutrients and shortening the screening time. The method inherits all the advantages of the traditional method, but is simpler and more reliable in operation.